Improvement on the Ability of Triple Standards Nursing Documentation through Case Reflection: A Pilot Study - Fibriansari, Rizeki Dwi; Maisyaroh, Arista; Kartono, Bambang Heri; Lestari, Tini (Fundamental and Management Nursing Journal, 2023)
Introduction: :The Indonesia National Nurses Association (INNA) has issued tiples national nursing documentations as a standard. Professional nurse's developments program was included set of interventions to increase the ability of nurses to implement the triple standards. Nevertheless, study on the program's evaluation was scarce. The study aims to find out the improvement of the ability of nurses to do documentation nursing by Triple standards through case reflection at a regional general hospital in Indonesia. Methods: A pilot project consisted with series of identifications was initiated. This included problem identification, problem analysis, and preparation of a Plan of Action (POA) was conducted. The research was set at a regional general referral hospital in Indonesia on 25 nurses with a purposive sampling technique. Data collection was carried out using interview and observation techniques related to the ability of nurses to carry out triple nursing documentation, then problem-solving used a case reflection discussion approach. Results: There is an enhancement ability of nurses in nursing diagnoses by SDKI standard by 56% after cases reflection was delivered. An increase of 28% was documented on the nurse's ability for the following sections: preparation of intervention and outcomes following the triple standards. Conclusions: Case reflections positively impact nurses' ability to implement a standardized nursing documentation. The program helps nurses more precise and structured in carrying out documentation according to 3S standards. Better and more accurate documentation can lead to more appropriate and quality care, and facilitate better communication between members of the healthcare team.